REVISITING THE DERADICALIZATION IN INDONESIA: A PROPOSAL FOR BETTER IMPLEMENTATION - Riyanta, Stanislaus; Rahayu, Amy YS; Mamoto, Benny J (UI Scholars Hub, 2021)
Terrorism has been one of the most concerning issues in Indonesia since it has penetrated all layers of society, including families and even police officers. Interestingly, some of the terrorist attacks have been launched by the ex-convicts of terrorism and this finding indicates that the deradicalization program, as one of the ways for mitigating the massive wave of terrorism, turns out to be ineffective. If this situation is not given proper attention, then in both the near and the far future it can be predicted that terrorism will be a recurrent theme of issues in the state. Therefore, there should be a concerted effort toward battling the terrorism and such concerted effort can be pursued through a collaboration between the academicians as part of civil society and the government. In relation to the statement, through this article the possible ways to involve the academicians in order to improve the implementation of the deradicalization program in Indonesia will be discussed in order to find the enlightenment that can deliver the better results.